Solution and Quasi-Bulk Copolymerizations of Styrene and Methyl Methacrylate in the Presence of Polybutadiene: Mathematical Model - Gutierrez, Carolina (2010)
A mathematical model was developed for simulating the batch copolymerization of styrene (St) and methyl methacrylate (MMA) in the presence of polybutadiene (PB). It was adjusted to the measurements of three reactions carried out at 65C, with initial comonomers ratio at the azeotropic condition, THF as solvent, and benzoyl peroxide as initiator. The measurements included: (a) conversions and grafting efficiencies by gravimetry; (b) molecular weight distributions (MWDs) by size exclusion chromatography; and (c) global mass fractions of St in the co- and terpolymer, by UV-Vis spectroscopy. The model predicts the MWDs of the three polymeric components of MBS: free St-MMA copolymer, St-MMA-g-PB graft terpolymer (GT), and residual PB. In addition, it predicts the bivariate chain length distributions of the different GT topologies, with each topology characterized by the number of branches per molecule.